An Authentication Scheme Using Locations and OAuth in IoT Environments - Cho, Jeong-Woo; Young Lee, Ki (International Journal of Engineering and Technology, 2018)
Recently, in the IoT environment, along with the emergence of many devices, the necessity of protected networks accessible only to certain users has been coming to the fore. Although network authentication systems can be more easily constructed by applying the OAuth protocol to IoT network environments for authentication, secondary authentication is recognized to be essential in the case of such systems because of the fact that such systems can be easily exposed to attacks when attackers have snatched the relevant token due to the characteristics of OAuth. Authentication through locations has the advantage that the user does not have to enter, remember, or carry any data. In addition, as the IOT advances, many APs are used leading to the improvement of the accuracy of WPS. Using the foregoing, this study is intended to enable user friendly authentication by taking the advantage of OAuth and using secondary authentication through location authentication, which is relatively convenient to users.Â Â